Initiation of The Edupreneurship Program in Building Interest as Kidspreneurs to Produce Agents of Change - Aprianti, Kartin; Yusuf, Muhammad; Mulyati; Ananda, Dea; Anggriani, Kiki (Universitas Putra Indonesia YPTK Padang, 2025)
The partner of the Beginner Community Empowerment Program (PMP) is the ITQ AR-Rahamn Elementary School in Bima City, which is committed to its vision of producing a generation that not only excels in science and technology to increase economic competitiveness but also has noble morals and a strong understanding of religion. Because the school's main focus is on strengthening religious and Qur'anic learning for students, the Principal hopes that students can have social knowledge and skills such as entrepreneurship so that they can have independence in society in the future. Through this grant program (PMP), together with partners, they carry out edupreneurship activities through motivational classes, coaching classes and creative classes as well as mentoring and program evaluation. Based on the evaluation results, it shows that 95.45% are happy with the product design activities with canvas and presenting in front of teachers and friends, 93% know how to prepare a simple business plan and 94% of participants are enthusiastic about becoming kidspreneurs. From the activities carried out by the PMP team, the E-module “Entrepreneurship Inspiration Project”, the E-Module “Successful Entrepreneurship Project”, the E-Module “My Business Mini Plan”, The E-Modul “Edupreneurship” and the “Kidsprenuer” Video were produced.